Prodromus of a fern flora for Bolivia. XL. Polypodiaceae - Smith, Alan R.; Kessler, Michael; León, Blanca; Almeida, Thaís Elias; Jiménez-Pérez, Iván; Lehnert, Marcus (Phytotaxa, 2018)
We provide a synopsis to the family Polypodiaceae in Bolivia, comprising 23 genera and 209 species, which renders this the most species-rich fern family in the country. Two large subfamilies are recognized, Polypodioideae, with 113 species in eight genera, and Grammitidoideae, with 95 species in 14 genera; a third subfamily, Platycerioideae, mostly paleotropical, is represented by one native species in the genus Platycerium. Two new combinations are made: Microgramma nana (Liebm.) T.E.Almeida and Pleopeltis burchellii (Baker) Hickey & Sprunt ex A.R.Sm.